Intelligence Reform Model as A Bridge to The Inflexibility of Bureaucracy Reforms Implementation in The State Intelligence Agency - Oktora Aditia; Roy V. Salomo (Universitas Muhammadiyah Gorontalo, 2021)
Every state intelligence organization is faced with the same problem in maintaining a balance between demands for accountability and openness with the confidentiality principle possessed by intelligence. The bureaucratic reform policy that forces all government agencies to apply the same standards, some of which are considered too rigid if implemented in the state intelligence agency.. Several criteria for assessing bureaucratic reform actually contradict the need for intelligence reform at the State Intelligence Agency (BIN), which is slowly tending to erode intelligence professionalism and secrecy to become more open, and have an impact on the weakening of the intelligence work system. This research will bridge the implementation of bureaucratic reform policies with the intelligence reform model so that the two can go hand in hand and strengthen each other. The method used in this research is the Systematic Literature Review (SLR) of journal articles published in the 2014-2019 period. Intelligence reform modeling is compiled based on the Research Question (RQ) related to policy objectives and intelligence typology. The results obtained from this study indicate that reform in intelligence organizations cannot be fully assessed using an evaluation worksheet of the implementation of bureaucratic reform, but rather prioritizes the ideal intelligence structure, intelligence secrecy, special surveillance, intelligence coordination, and effectiveness of intelligence operations. This research needs to be interpreted as merely a form of commitment and seriousness of researchers to participate in efforts to build a more professional intelligence community following the principles of democracy, upholding law, and human rights.